Towards a conceptual framework of animated infographics in an Islamic context / Nur Nazihah Rahim … [et al.] - Rahim, Nur Nazihah (2015)
Animated infographics become increasingly popular because it's appealing the eyes of the audience rather than words alone. Researchers found that the human brain can process faster when they are seeing the visual images. Today, people are live in a rich of the information age and the digital era. Somehow, information mixing create some problems such as confusing and difficult in recalling the information. Thus, people are not clearly understood the information have given. Therefore, animated infographics could be a solution in disseminating the information effectively. Animated infographics are able to convey much more information with successive images compared with still images. Nevertheless, animated infographics in Islamic context or in other word, animated Islamographics become one of the alternative ways to understand the Islamic knowledge in this era of Information and Communication Technology (ICT). Unfortunately, a very limited studies focus on the specific context of animated infographics, and there might be some significant contribution to the body of knowledge. Additionally, ICT should become a tool used by the users that corresponding with maqasid shari’ah (purpose of Shari’ah), which is dururiyyat (five basic necessities) such are religion, life, intellect, lineage and property. In terms of religious observance, ICT can help in spreading the message of Islamic faith and theology more broadly. This study is meant to conduct a critical review of various studies to conceptualize the framework for animated infographics in implementing Islamic context for the Muslim in Malaysia. Content analysis method was used towards the development of the conceptual framework. Furthermore, the conceptual framework would be used a basis for more new discoveries in line with this area of the study.